An Automated Clinical Information System - Yoder, D. Richard; Swearingen, R. Dorothy; Schenthal, E. Joseph; Sweeney, W. James; Nettleton, J. Wilson, Jr (Methods of Information in Medicine, 1964)
An automated clinical record system must have the following characteristics: as far as the physician is concerned it must operate in natural language on standard sized paper; it must be able to accept information from the physician at a time when he is oriented to clinical terminology and a clinical mode of thinking; it must have an output which is clinically useful for the care and management of a patient; each item of information must be addressable so that it may act as an index for scientific information retrieval; it must be capable of accepting quantative and natural language information.Clinical information constitutes a mathematical set, only a few members of which are applicable to any particular clinical situation, and to which new members are constantly being added. The members of this set are seldom mutually exclusive. An acceptable system which is capable of processing this type of information has been designed utilizing the concepts of self-encoding forms and variable-field, variable-length records. Applications of these principles will expedite hospital automation, the establishment of drug evaluation information systems, and of regional and nationwide medical record systems.Ein automatisiertes klinisches Datenerfassungssystem muß folgende Eigenschaften aufweisen: Soweit der Arzt angesprochen wird, soll dies in der üblichen Schriftsprache auf genormtem Papierformat geschehen; andererseits muß das System Informationen von Seiten des Arztes verstehen, wenn dieser sich einer klinischen Denkweise und der klinischen Terminologie bedient; die Ergebnisse müssen in einer für die Pflege und Behandlung des betreffenden Patienten klinisch brauchbaren Form ausgegeben werden; jede Einzelinformation muß exakt adressierbar sein, so daß sie auch als Index für ein wissenschaftliches “information retrieval” dienen kann; schließlich muß das System sowohl quantitative Informationen als auch solche in natürlicher Sprache verarbeiten können.Klinische Information besteht aus einer mathematischen Menge, von der nur wenige Teilmengen auf die jeweilige klinische Situation anwendbar sind und zu der ständig weitere Elemente hinzukommen. Die Elemente dieser Menge schließen sich nur selten gegenseitig aus. Die Verfasser haben unter Benutzung maschinell verschlüsselbarer Formulare und Krankengeschichten mit variabler Feldlänge ein System entwickelt, das Informationen dieser Art verarbeiten kann. Die Anwendung dieser Prinzipien wird die Automatisierung im Krankenhaus, die Schaffung von Arzneimittel-Beurteilungssystemen und den Aufbau einer regionalen und nationalen medizinischen Befunddokumentation fördern.